The correlation between emotional intelligence and clinical competence in nurses working in special care units: A cross-sectional study - Dehnavi, Mohammad; Estebsari, Fatemeh; Kandi, Zahra Rahimi Khalifeh; Milani, Arezoo Sheikh; Hemmati, Mahshid; Nasab, Abdollah Farhadi; Mostafaie, Davoud (Nurse education today, 2022)
Emotional intelligence and clinical competence are essential skills of the nursing profession to elevate the quality of nursing services and patient satisfaction. This study aimed to determine the correlation between emotional intelligence and clinical competence in nurses working in critical care units of hospitals affiliated to Shahid Beheshti University of Medical Sciences. A cross-sectional study with a correlational design. Special care units (SCUs) of hospitals affiliated to Shahid Beheshti University of Medical Sciences in Tehran, Iran. The research subjects included 200 nurses working in the Special care units SCUs of hospitals affiliated to Shahid Beheshti University of Medical Sciences, selected via convenience sampling. Data were collected using three questionnaires, including a demographic information questionnaire, the Bar-On Emotional Quotient Inventory (EQ-i), and Benner's Nurse Competence Scale (NCS). The questionnaires were completed from October to December 2019. Data were analyzed using SPSS-18 software at a significance level of P < 0.05. The emotional intelligence of nurses participating in the study had the highest mean (SD) of 17.31(3.34) in the self-expression dimension and the lowest mean of 12.04(3.40) in the empathy dimension. There was a significant direct correlation between emotional intelligence and clinical competence (P = 0.05). There was also a significant relationship between the total clinical competence and its dimensions (P < 0.05). Communication skills and accountability significantly impact the provision of optimal care, and the proper training of staff in responsibility, accountability, and communication skills will have many benefits for promoting nursing services and can be considered one of the strategies to improve the quality of nursing services. They are therefore recommended to be considered in designing and implementing continuing education programs for nurses.